Management of bladder cancer recurrence following the trimodality therapy - Damaj, Nahed; Naim, Nabih; Saad, Ahmad; Kattan, Clarisse; Kattan, Joseph (Frontiers in Oncology, 2025)
Trimodality therapy (TMT), including transurethral resection (TUR), chemotherapy (CT), and radiotherapy (RT), offers the bladder-preserving treatment option for patients with muscle-invasive bladder cancer (MIBC). TMT, once indicated, has demonstrated effective and favorable local tumor control in MIBC, with complete response rates ranging between 50% and 80%. However, residual tumor is identified on follow-up TUR in approximately 20–30% of patients, and tumor recurrence occurs in a similar proportion. In both situations, the prognosis becomes unfavorable. This manuscript reviews the current evidence regarding recurrence patterns after TMT, differentiating between non–muscle-invasive (NMIBC) and muscle-invasive (MIBC) relapses. NMIBC recurrences after TMT are often manageable with conservative treatments like repeat TURBT and intravesical BCG, without negatively impacting survival. In contrast, MIBC recurrences typically require salvage cystectomy in fit patients, offering outcomes similar to primary surgery. For those unfit for or who continue to decline cystectomy, treatment remains uncertain due to the absence of clear guidelines, and systemic therapies used in metastatic urothelial carcinoma seem commonly applied by extrapolation.